Understanding medical aspects of violent crimes in Sweden’s region Skåne: a retrospective cross-sectional design of the ViCS project - Ringqvist, Alexandra; Aloumar, Basem; Wingren, Carl Johan; Ekelund, Ulf; Khoshnood, Ardavan M. (Frontiers in Psychiatry, 2023)
While there has been a reduction in specific homicide categories in Sweden, the last decade has witnessed an increase in the overall rate. The escalation is predominantly linked to heightened gun violence associated with criminal gangs. As a result, Sweden faces an extreme rate of shootings and firearm-related homicides, constituting one of the most severe instances across Europe. However, comprehensive scientific studies on this phenomenon are lacking. This paper presents the design of the Violent Crimes in Skåne (ViCS) project, which aims to investigate violent crimes requiring hospitalization or causing death in Sweden´s region Skåne from a medical, forensic, and criminological perspective. The project aims to examine the epidemiology and trends of violent crimes, injury profiles, treatments, patient outcomes, causes of death, and victim demographics.Methods and analysis: Using a retrospective cross-sectional design, ViCS will examine trauma by violent crimes from 2000 to 2019. Data will be sourced from several institutions, including hospital records from nine emergency hospitals, and the National Board of Forensic Medicine Agency. The project aims to study medical and criminological aspects of violent crimes, primarily focusing on assaults involving firearms, sharp weapons, blunt instruments, kicks, punches, and other types of assault like strangulation. Data analysis will involve descriptive and inferential statistics. Discussion: ViCS aims to contribute to the limited body of knowledge about victims of violent crimes in Sweden. The findings may inform evidence-based interventions in medical, forensic, and criminological fields, potentially enabling targeted prevention strategies and improvements in emergency care for victims.